Performance enhancing method of coral aggregate for preparing concrete
The ultrafine cement slurry is filled into the pores of coral aggregates through negative pressure vacuum technology, which solves the problems of low mechanical strength and poor durability of coral aggregate concrete, significantly improves its density, mechanical strength and permeability resistance, and is suitable for complex marine environments.
Patent Information
- Application Number
- CN202411948538.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-25
AI Technical Summary
Coral aggregate concrete has low mechanical strength and poor durability, especially in marine environments, which are difficult to meet the application needs in complex environments.
The ultrafine cement slurry is sucked into coral aggregate through negative pressure vacuum technology to fill its pore structure, thereby enhancing its mechanical strength and anti-seepage properties.
It effectively improves the compactness, mechanical strength and permeability of coral aggregates, improves the overall performance of concrete, and enables it to better adapt to complex conditions of the marine environment.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coral aggregate modification for concrete, and in particular relates to a method for enhancing the performance of coral aggregate used for preparing concrete. Background Art
[0002] In the civil engineering of marine development and island construction, corals are used as building aggregates. Not only can they be sourced locally, saving material and transportation costs, but the structures they build have the advantage of being better able to adapt to rising sea levels and ocean climate change. During World War II, corals were used to mix concrete for the construction of airports, roads and buildings on Pacific islands and reefs. Therefore, coral aggregates have very good application value in island construction.
[0003] The mineral composition, pore structure and particle morphology of corals result in significant differences in their performance from general sand and gravel aggregates. The main crystal forms of corals are carbonate minerals such as aragonite, calcite and magnesium calcite, and the main chemical component, calcium carbonate, accounts for more than 96%. Compared with general quartz sand, coral aggregates have the characteristics of low particle strength, easy breakage, loose structure, porous and interconnected, and relatively small volume and mass. These characteristics will significantly affect the mechanical properties of concrete prepared with corals. For example, compared with ordinary concrete, coral concrete has lower strength and exhibits early strength characteristics. It is difficult to produce coral concrete with a strength grade exceeding C30 using traditional methods. The high porosity and good pore connectivity of corals result in poor impermeability and good water absorption capacity of concrete prepared from corals, which seriously affects the durability of coral concrete, such as resistance to chloride and sulfate erosion.
[0004] At present, there are some measures that can optimize the mechanical strength and durability of coral concrete, including the addition of mineral admixtures (fly ash, blast furnace slag, silica fume, metakaolin, etc.), the addition of various fiber materials (sisal fiber, polypropylene fiber, carbon fiber, glass fiber, etc.), and the pretreatment of coral aggregate (such as slurry wrapping, negative pressure inhalation enhancer, or early acid treatment or organic solution coating modification). These measures are helpful to the modification of coral concrete to a certain extent, but they also have disadvantages to varying degrees. For example, the addition of mineral admixtures and fiber materials cannot change the porous structural characteristics of the coral aggregate itself; acid or organic solution treatment has a certain corrosive effect on coral aggregate, and the solution concentration is difficult to control; slurry wrapping cannot compact the aggregate pore structure; negative pressure inhalation enhancer will destroy the original structure of the coral and thus affect the durability of the aggregate, and will also affect the bonding ability between the coral aggregate and the cement paste when preparing concrete.
[0005] Based on the above problems, the current methods are difficult to solve the problem of low strength and poor durability of concrete cast with coral as building aggregate. In order to ensure that coral concrete can be widely used in complex marine environments, a method is needed to compact the pore structure of coral aggregate and improve its mechanical strength and impermeability without affecting the original structure of coral aggregate, so as to facilitate better use in the preparation of concrete. Summary of the invention
[0006] The object of the present invention is to provide a method for enhancing the performance of coral aggregate used for preparing concrete, which can compact the pore structure of coral aggregate and improve its mechanical strength and anti-permeability performance.
[0007] In order to achieve the above object, the present invention adopts the following technical solution: A method for enhancing the performance of coral aggregate for concrete, comprising the following steps: Step 1, cleaning and drying the coral aggregate; wherein the coral aggregate is coarse coral aggregate with a particle size greater than 4.75 mm.
[0008] Step 2, place the coral aggregate in a sealed container, use an air pump to suck out the air in the container until the pressure in the container is -0.1MPa, turn off the air pump, and let it stand to ensure that the air inside the coral aggregate is discharged so that the internal pores are also in a vacuum state; Step 3, fully mixing the ultrafine cement, the water reducing agent and water to prepare a cement slurry for grouting; Step 4, slowly sucking the cement paste into the container under vacuum negative pressure conditions to ensure that the paste fully buries all the coral aggregates; Step 5, turn off the air pump and let it stand to ensure that the cement slurry fully buries the coral aggregate; Step 6, opening the container and continuing to stand for treatment so that the cement slurry can be pressed into the pores of the coral aggregate under the action of atmospheric pressure; Step 7, scooping the coral aggregate out of the slurry, separating the coral aggregate from the excess slurry by sieving, and placing the coral aggregate in the air for static treatment after separation until the cement reaches an initial setting state; Step 8, sieving the coral aggregate again to separate the excess cement paste; Step 9, curing the coral aggregate after the two screening and separation; Step 10, sieving the cured coral aggregate again to obtain.
[0009] Among them, in the above-mentioned method for enhancing the performance of coral aggregate for concrete, the container described in step 2 is airtight, connected to an air pump and a pressure gauge, and has the ability to adjust and monitor the pressure in the container.
[0010] Preferably, the standing time in step 2 is at least 24 hours to ensure that the air in the pores of the coral aggregate is sucked away.
[0011] Preferably, in step 3, the water-cement ratio in the cement paste is 1-1.2:1; and the amount of the water reducer is 0.2%-0.4% of the mass of the cement.
[0012] More preferably, the fineness index D50 of the ultrafine cement is within 5 μm.
[0013] More preferably, the water reducer is required to have the characteristics of water reduction, enhancement, slow setting, high efficiency, and fine particle size. The water reducer is a polycarboxylic acid water reducer, and more preferably Sika 325C polycarboxylic acid high-efficiency water reducer.
[0014] Preferably, in step 4, the cement slurry is sucked into the container at a speed that ensures that the pressure in the container always remains at -0.1 MPa.
[0015] Preferably, in step 5, the standing time is 30 to 45 minutes.
[0016] Preferably, in step 6, the standing time is 1 to 1.25 hours.
[0017] Preferably, in step 7, the nominal diameter of the sieve hole is 4.75 mm.
[0018] Preferably, in step 7, the standing time is 2 to 3 hours, during which a portion of the cement slurry is still pressed into the coral aggregate under the action of atmospheric pressure.
[0019] Preferably, in step 8, the nominal diameter of the sieve hole is 4.75 mm.
[0020] Preferably, in step 9, the curing environment is 25° C., normal pressure, and 95% relative humidity, and the curing period is 28 days.
[0021] Preferably, in step 10, the nominal diameter of the sieve hole is 4.75 mm.
[0022] The present invention further provides the use of the coral aggregate with enhanced performance obtained by the above method in preparing concrete.
[0023] Compared with the prior art, the present invention has the following beneficial effects: The present invention utilizes negative pressure to absorb ultrafine cement paste into coral aggregate to fill pores, which can effectively improve the problem of loose pores in coral aggregate. The cement paste and coral skeleton work together to provide strength, thereby enhancing the density, mechanical strength and impermeability of coral aggregate. The ultrafine cement paste as a filler will not affect the chemical properties of coral aggregate, and the coral aggregate strengthened by slurry absorption will not change the chemical characteristics of concrete as a mixing material, and has good bonding force with the cement paste. DETAILED DESCRIPTION
[0024] The present invention is further described in detail below with reference to specific embodiments, but is not intended to limit the present invention.
[0025] The water reducing agent described in the following embodiments of the present invention is a polycarboxylic acid high-efficiency water reducing agent (Sika 325C). Example 1
[0026] Ultrafine cement has poor rheological properties and fast hydration speed. In order to ensure that the cement paste is fully poured into the coral aggregate before solidification, this embodiment investigates the cement paste for grouting. The specific cement paste ratio is shown in Table 1, where the water-cement ratio is the water / cement mass ratio, and the amount of water reducer is added according to the mass percentage of the cement amount.
[0027] The fluidity was measured according to GBT8077-2023 cement mortar fluidity determination method. The initial setting time was measured according to GB / T 1346-2011. The compressive strength and flexural strength were measured according to GB / T 17671-2021. The results are shown in Table 2.
[0028] Table 1 Cement paste ratio scheme
[0029] Table 2 Cement paste performance test
[0030] From the results in the table, it can be seen that with the increase of water-cement ratio, the initial setting time and fluidity increase, but the compressive strength and flexural strength gradually decrease. The larger the particle size of ultrafine cement, the more difficult it is for the slurry to absorb into the coral pores, and the prepared cement slurry has lower compressive strength and flexural strength. Adding water reducer can not only improve the fluidity of cement slurry, prolong the initial setting time, but also further enhance its compressive strength and flexural strength.
[0031] In order to facilitate the grouting of coral aggregate, cement paste with good fluidity and long initial setting time is selected; considering the mechanical strength, on the basis of the same fluidity and initial setting time, the cement paste for grouting can give priority to the mix ratio scheme with a larger amount of water reducer, rather than the mix ratio scheme with a larger water-cement ratio. Therefore, the initial grouting schemes 3, 4, and 9 are selected as cement pastes for grouting. Example 2
[0032] The coral aggregates taken from the South China Sea were cleaned, dried in an oven at 105°C for 6 hours, and cooled to room temperature. The particle size distribution of the coral aggregates was 4.75~30mm.
[0033] Weigh 6kg of coral aggregate and put it in a sealed container. Use an air pump to suck out the air in the container until the pressure in the container is -0.1MPa. Turn off the air pump and ensure that the coral aggregate is left standing in an environment with an air pressure of -0.1MPa for 24 hours to ensure that the air inside the coral aggregate is sucked out and the internal pores are also in a vacuum state.
[0034] The ultrafine cement, water and water reducing agent are fully mixed in a mass ratio of 1:1:0.4% to prepare cement slurry for grouting. The ultrafine cement is Panlongshan K1340, and its fineness index D50=4.555.
[0035] Turn on the air pump and slowly suck the mixed cement slurry into the container to ensure that the coral aggregates are fully buried by the slurry. During the slurry suction process, ensure that the pressure in the container is always maintained at -0.1MPa. Then turn off the air pump and let the coral aggregates buried by the slurry stand in a -0.1MPa pressure environment for 30 minutes to ensure that the slurry fully buries the aggregates.
[0036] Open the container and place the coral aggregate fully buried by the slurry in a normal atmospheric pressure environment for 1 hour to ensure that the slurry can be pressed into the pores of the aggregate under the action of atmospheric pressure.
[0037] The coral aggregates were scooped out from the slurry and separated from the excess slurry by screening with a 4.75 mm mesh. After separation, the coral aggregates were placed in the air for 2.5 hours to allow the slurry to be pressed into the aggregates under the action of atmospheric pressure.
[0038] The coral aggregate was screened again through a 4.75 mm sieve to separate the excess cement paste.
[0039] The coral aggregates separated by two screenings were placed in a curing box for 28 days. The curing environment was a temperature of 25°C, normal pressure, and a relative humidity of 95%.
[0040] Take out the cured coral aggregate and sieve it through a 4.75mm screen again to separate the excess cement slurry for later use. Example 3
[0041] The difference between this embodiment and embodiment 2 is that ultrafine cement, water and water reducing agent are fully mixed in a mass ratio of 1:1.2:0.2% to prepare cement slurry for grouting, and the rest is the same as embodiment 1. Example 4
[0042] The difference between this embodiment and embodiment 2 is that ultrafine cement, water and water reducing agent are fully mixed in a mass ratio of 1:1:0.2% to prepare cement slurry for grouting, and the rest is the same as embodiment 1. Comparative Example 1
[0043] The difference between Comparative Example 1 and Example 2 is that the air in the container is sucked away by an air pump until the pressure in the container is -0.05 MPa, and the pressure in the container is always kept at -0.05 MPa during the subsequent slurry suction process. After the air pump is turned off, the coral aggregate buried by the slurry is placed in a -0.05 MPa pressure environment, and the rest is the same as Example 2. Comparative Example 2
[0044] The difference between Comparative Example 2 and Example 2 is that no air pump is used to suck out the air in the container, and the pressure of the environment where the coral aggregate is located is always atmospheric pressure during the entire test process. Other aspects are the same as Example 2.
[0045] The density, mechanical strength and anti-seepage performance of the coral aggregate before and after slurry absorption in the above embodiments and comparative examples were tested. The test method and test results are as follows: (1) Five coral aggregates were taken and their porosity was tested before and after grouting using the vacuum saturation method. The results were taken as the average value of the five samples.
[0046] (2) Take three portions of coral aggregate after grouting and three portions of coral aggregate without grouting, each weighing 1.5 kg, and place them in a crushing index measuring instrument. The crushing index measuring instrument is placed under a press with a peak pressure of 150 kN for crushing test. The crushed coral aggregate is sieved through a 4.75 mm sieve, and the mass proportion of coral aggregate with a particle size of less than 4.75 mm after crushing is calculated. The result is the average of the three samples.
[0047] (3) Take 5 coral aggregates and immerse them in clean water for 30 minutes before and after slurry absorption. Calculate the mass increase rate after immersion to reflect the anti-seepage ability. The result is the average value of the 5 samples.
[0048] Table 3 Comparison of coral aggregate performance before and after grouting
[0049] The method disclosed by the present invention can effectively improve the loose pore characteristics of coral aggregate, thereby enhancing the density, mechanical strength and anti-seepage performance of the coral aggregate.
[0050] The above embodiments are only for illustrating the technical idea of the present invention, and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the present invention.
Claims
1. A method for enhancing the performance of coral aggregate for concrete, characterized in that: The steps include: (1) Place the coral aggregate in a sealed container, use an air pump to extract air until the container is in a vacuum environment, turn off the air pump, and let it stand to allow the air inside the coral aggregate to be discharged; (2) Fully mix the ultrafine cement, water reducing agent and water to prepare cement paste for grouting; (3) Suck the cement paste into the container under vacuum and negative pressure until all the coral aggregates are fully buried; let it stand; (4) Open the container and continue to stand for a while, so that the cement paste can enter the pores of the coral aggregate under the action of atmospheric pressure; (5) The coral aggregate is scooped out from the slurry, and is subjected to primary screening, primary coagulation, secondary screening, curing, and screening to obtain coral aggregate with enhanced performance.
2. The method for enhancing the performance of coral aggregate for concrete according to claim 1, characterized in that: In step (1), the coral aggregate is coarse coral aggregate; and / or the coral aggregate is cleaned and dried.
3. The method for enhancing the performance of coral aggregate for concrete according to claim 1, characterized in that: The standing time in step (1) is more than 24 hours.
4. The method for enhancing the performance of coral aggregate for concrete according to claim 1, characterized in that: In the cement paste described in step (2), the water-cement ratio is 1-1.2:1; and the amount of the water reducer is 0.2%-0.4% of the cement mass.
5. The method for enhancing the performance of coral aggregate for concrete according to claim 1, characterized in that: The fineness index D50 of the ultrafine cement described in step (2) is within 5 μm.
6. The method for enhancing the performance of coral aggregate for concrete according to claim 1, characterized in that: The water reducing agent in step (2) is a polycarboxylic acid water reducing agent.
7. The method for enhancing the performance of coral aggregate for concrete according to claim 1, characterized in that: The standing time in step (3) is 30 to 45 minutes.
8. The method for enhancing the performance of coral aggregate for concrete according to claim 1, characterized in that: The standing time in step (4) is 1 to 1.25 hours.
9. The method for enhancing the performance of coral aggregate for concrete according to claim 1, characterized in that: The screening, re-screening and sieving in step (5) are performed by using a sieve with a nominal mesh diameter of 4.75 mm.
10. Use of the coral aggregate with enhanced performance prepared by the method according to any one of claims 1 to 9 in preparing concrete.